Effects of livestock grazing on physical and chemical properties of sandy soils in Sahelian rangelands - Hiernaux, Pierre H.Y.; Bielders, Charles L.; Valentin, Christian; Bationo, B. André; Fernández Rivera, S. (Elsevier, 1999)
The effects of 4 years grazing by sheep and goats at various stocking rates on soil surface features, bulk density, organic C, N and P contents and pH were investigated in Sadore, Niger. Studies were also conducted in a fallow subjected to 9 years of intensive grazing. Although grazing reduced (P<less than>0.001) and fragmented the area of crusted soil, the infiltration index increased with moderate grazing, and decreased at high stocking rates. The bulk density of topsoil was lower under shrub canopy but remained unchanged in deeper horizons. Organic C, N and P contents, water infiltration and biological activity were greater in soils sheltered by shrubs than in bare soil. On the site intensively grazed for 9 years, P content was lower and N and organic C contents higher than after 4 years under controlled grazing. Compaction occurred only in the topsoil beneath shrub canopy and vegetated patches under intensive grazing.